Design and Cogging Torque Reduction of Radial Flux Brushless DC Motors with Varied Permanent Magnet Pole Shapes for Electric Vehicle Application (2023)
Brushless direct current motors have more attractive features, making them a promising solution for electric vehicle applications. A 1 kW, 510 rpm, 24-slots and 8-pole inner runner type surface permanent magnet mounted radial flux brushless DC motor with seven different permanent magnet pole shape rotor is investigated. Motors with different permanent magnet shape rotors were designed, and finite element modelling and simulation were carried out. For performance comparison, the initial design with a radial-type pole shape was regarded as a reference design. Cogging torque is detrimental to the overall performance of the motor, typically in low-speed applications like electric vehicles. The primary aim of this paper is to reduce the cogging torque & study its effect on the overall performance of the motor and minimize torque ripples with reduced permanent magnet requirements. The proposed designs are analyzed in terms of cogging torque, flux density, torque, efficiency, flux linkage and back-EMF. The comparative analysis shows that the motor with bump-shaped permanent magnet rotor poles has betterperformance than the others.